Analysis of Regional Financial Independence and Capability and Their Implications for Inclusive Economic Growth in Mojokerto Regency, 2014–2023 - Febrianata, Zekha; Athoillah, Moh (Journal of Development Economic and Social Studies, 2025)
The shift in policy direction from centralization to decentralization requires each region to become self-sufficient by generating more Local Own-Source Revenue (PAD) than the transfer funds provided by the Central Government. This study aims to determine the level of regional financial independence and capability and their impact on inclusive economic growth in Mojokerto Regency for the fiscal years 2014–2023. The data analysis methods used are the regional financial capability ratio and the regional independence ratio, followed by multiple linear regression analysis to assess their impact on inclusive economic growth. The results show that the regional independence ratio of Mojokerto Regency remains in the low category, with an average of 36.70%. Meanwhile, the regional financial capability ratio indicates a moderate result, with an average of 22.27%. The regional independence variable has a positive but insignificant relationship with inclusive economic growth, while the regional financial capability variable has a negative and significant effect on inclusive economic growth.